2017
DOI: 10.1038/s41598-017-03590-3
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the inflammatory cytokines and brain-derived neurotrophic factor contribute to depression-like phenotype after spared nerve injury: improvement by ketamine

Abstract: Although pain is frequently accompanied with depression, little is known about the risk factors contributing to individual differences to the comorbidity of pain and depression. In this study, we examined whether cytokines and brain-derived neurotrophic factor (BDNF) might contribute to the individual differences in the development of neuropathic pain-induced depression. Rats were randomly subjected to spared nerved ligation (SNI) or sham surgery. The SNI rats were divided into two groups by the data from depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 82 publications
4
43
0
Order By: Relevance
“…We found decreased BDNF-TrkB signaling in the mPFC and hippocampus from rats with anhedonia-like phenotypes on day 23 after SNI, consistent with the previous study [31]. Low levels of BDNF in the mPFC are associated with the development of depression-like phenotypes including anhedonia in rodents [19][20][21][22][23][24][25][26][27][28]41].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…We found decreased BDNF-TrkB signaling in the mPFC and hippocampus from rats with anhedonia-like phenotypes on day 23 after SNI, consistent with the previous study [31]. Low levels of BDNF in the mPFC are associated with the development of depression-like phenotypes including anhedonia in rodents [19][20][21][22][23][24][25][26][27][28]41].…”
Section: Discussionsupporting
confidence: 78%
“…The previous clinical studies demonstrated that the incidence of comorbid chronic pain and depression is around 30-50% [1,4,5], which is in line with the present study. In this study, we found that rats with or without anhedonia-like phenotypes showed similar mechanical withdrawal thresholds, suggesting that the alterations in mood-related behaviors were independent of the degree of nociceptive damage, consistent with the previous studies [8,31,[38][39][40].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The precise mechanisms underlying antidepressant actions of ketamine and ( R )-ketamine are not fully understood. It has been suggested that anti-inflammatory actions of ketamine might play a role in its antidepressant effects 62 65 . Given the role of gut microbiota in the immune system 33 35 , 42 , 66 , it is likely that anti-inflammatory action of ( R )-ketamine might play a role in its antidepressant effects through the immunomodulation by the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…In rat models of depression, low‐dose ketamine acutely influences anti‐inflammatory pathways thought to be neuroprotective. Ketamine reduces hippocampal and serum levels of pro‐inflammatory cytokines IL1β, IL6 and TNFα while concurrently reducing depressive symptoms (N. Wang et al, ; Xie et al, ). This culminates in an overall reduction in ROS (Demirdas, Naziroglu, & Ovey, ).…”
Section: Resultsmentioning
confidence: 99%